Fetal outcome of operative delivery and its risk factors in Sardjito Hospital - Risanto Siswosudarmo, Risanto Siswosudarmo (Universitas Gadjah Mada, 1990)
A study on operative delivery was carried out during the period of 1988 to find out the fetal outcome and some of the risk factors. A cohort study was used, consisting of the exposed group (operative delivery, 212 cases) and the control group (spontaneous delivery, 212 cases) selected randomly using a computer generated random number. Only singleton pregnancy, gestational age 28 weeks or more or birthweight 1000 g or more were included into the study. All babies were followed up during their neonatal period in the neonatal care unit. Neonatal morbidity was defined as asphyxia, birth traumata and diseases such as fever, vomiting etc. found during the early neonatal period. Data were processed with IBM personal computer using version 2.0 SPSS program. t-test, chiÃ¢â¬âsquare test and relative risk were statistical analyses used in this study.Result showed that the incidence ofoperative delivery during that period was 24.62%. The most common one was cesarean section (39.2%) and the least common was internal podalic version and laparotomy (1.9%). Age more than 30 years, parity more than two (gravidity more than three) and referral cases seemed to be the risk factors for termination of delivery by an operative procedure.The risk of deliveringasphyxic babies was much more common in the exposed group compared to the control. The rate of severely asphyxic babies was 50.5% compared to only 5.9% and the rate of slight asphyxia was 38% compared to 11.3% respectively for the exposed and control groups. Mean one minute Apgar score was 3.87 vs 7.29 and mean five minutes Apgar score was 6.89 vs 9.15. The number of babies suffering from one or more morbidities were 94.0% in the exposed group vs23.6% in the control group. There was a significant difference in term of perinatal mortality but not in neonatal mortality, although it seemed to be clinically important.The study concluded that although fetal outcome in the operative delivery was worse, but with careful maneuver and intensive neonatal care the risk of neonatal mortality could be minimized.Key Words: high-risk labor - operative delivery - perinatal morbidity and mortality - asphyxic babies Apgar score